The influence of interstage channel on efficiency of molecular drag stage in hybrid turbomolecular pump - J. A. Shostak; N. K. Nikulin; G. T. Tsakadze; P. A. Shostak; A. M. Shostak (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The interstage channel is one of the factors affecting the efficiency of the molecular drag stage in a hybrid turbomolecular pump (TMP). The influence of parameters of the channel on the pumping performance of the molecular drag stage is investigated. The offered approach allows calculating the pumping performance of a molecular drag stage taking into account the effect of the interstage connecting channel on the pumping process. The comparison of the pumping characteristics of a molecular drag stage obtained in calculation taking into account the effect of the channel and excluding it is given. This article assesses the efficiency of the molecular drag stage in a hybrid TMP depending on geometric and dynamic parameters of the channel. The outcomes and recommendations allow to expand the range of working pressures of a hybrid TMP exclusively by means of parameters of the connecting channel.